Bamlanivimab and Etesevimab Improve Symptoms and Associated Outcomes in Ambulatory Patients at Increased Risk for Severe Coronavirus Disease 2019: Results From the Placebo-Controlled Double-Blind Phase 3 BLAZE-1 Trial. (7th April 2022) - Chen, Peter; Behre, Gerhard; Hebert, Corey; Kumar, Princy; Farmer Macpherson, Lisa; Graham-Clarke, Peita Louise; De La Torre, Inmaculada; Nichols, Russell M; Hufford, Matthew M; Patel, Dipak R; Naegeli, April N
Abstract: Background: In the phase 2/3 BLAZE-1 trial, bamlanivimab and etesevimab together reduced coronavirus disease 2019 (COVID-19)–related hospitalizations and any-cause mortality in ambulatory patients. Herein, we assess the impact of bamlanivimab and etesevimab treatment on the severity and length of symptoms and health outcomes among patients at increased risk for severe COVID-19. Methods: In the phase 3 portion of BLAZE-1 (NCT04427501), symptomatic patients with increased risk for severe COVID-19 were randomized (2:1) to a single infusion of 700 mg bamlanivimab and 1400 mg etesevimab or placebo. Hospitalization events, vital signs, and symptomatology were monitored throughout the trial. Results: Overall, 769 patients were randomized to bamlanivimab and etesevimab together (n = 511) or placebo (n = 258). The time to sustained symptom resolution was significantly shorter among patients who received bamlanivimab and etesevimab compared with placebo (8 vs 10 days; P  < .01). The median time to first sustained symptom resolution of body aches and pain, chills, fatigue, feeling feverish, headache, and shortness of breath was significantly different in patients receiving bamlanivimab and etesevimab compared to placebo ( P  < .05). The proportion of patients who experienced COVID-19–related hospitalization by day 29 was significantly reduced among the bamlanivimab and etesevimab group compared with placebo (0.8% vs 5.4%; P  < .01). The mean duration of hospital stay was numerically shorter among patients who received bamlanivimab and etesevimab (7.3 vs 13.5 days; P  = .16), with fewer intensive care admissions. Conclusions: Patients receiving bamlanivimab and etesevimab together resolved their symptoms more rapidly than those receiving placebo. Bamlanivimab and etesevimab treatment was associated with reduced rates of hospitalizations and shorter hospital stays. Clinical Trials Registration: NCT04427501. Abstract : Among patients with mild to moderate COVID-19 at high risk for developing severe disease, bamlanivimab and etesevimab reduced rates of hospitalizations and intensive care admissions, reduced lengths of hospitalizations, and shortened times to sustained symptom resolution.